ACESSO À SAÚDE DA MULHER NA ATENÇÃO PRIMÁRIA: MARCADORES E INTERSECCIONALIDADES - Barbosa, Bruna Ligia Ferreira de Almeida (2021)
Introduction: The reality about the health problems that women have been experiencing in Brazil, evidences the denial of comprehensiveness, insofar as it requires embracement, sensitive listening, access, continuity, and resolution. The existence of social markers, whether of race, economic, social, and educational status, places women in a situation of vulnerability, reflecting on access to Primary Health Care services. In this perspective, considering that women are the majority among the Primary Health Care users, their experiences must be contextualized, respecting the singularities and recognizing their conditions of vulnerability, in order to alleviate the inequalities that interfere in the access and use of health services. Objective: Analyse the access to and utilization of services aimed to women’s health into the Primary Health Care system in the state of Espírito Santo. Methodology: Descriptive study, with a qualitative approach, carried out in women users of Primary Health Care, from October 2020 to January 2021, in five municipalities that represent the health regions of Espírito Santo, plus the capital Vitória. A questionnaire with sociodemographic information of the users and a script guided by the theoretical framework of access and use of health services by McIntyre and Mooney (2007) was used. For data analysis, the Thematic Analysis technique by Bardin (2011) was used, which consists of three stages: data pre-analysis, resource exploration, and data interpretation. Results: Barriers were identified with regard to availability, acceptability and ability to pay for access to services offered in Primary Health Care. These barries are present mainly in relation to referral to specialized services, reception, health promotion actions and diagnostic tests. In addition, the different levels of information between the service teams and the users, were related to a greater or lesser extent to the access and use of health services, especially regarding mammography. Final considerations: There are factors that interfere with access to primary care services, reflecting the inequalities among women. The race/color, gender and social class cuts reflect and reveal the structural/institutional racism that shapes our society, highlighting the inequalities faced by women when accessing, among others, health services.Propositional strategies for reorganizing women's health policies are necessary in order to overcome barriers and enable greater access and use of women to primary care services.